2017
DOI: 10.1037/adb0000271
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Behavioral Strategies for Marijuana Scale: Further examination using item response theory.

Abstract: Given recent state legislation legalizing marijuana for recreational purposes and majority popular opinion favoring these laws, we developed the Protective Behavioral Strategies for Marijuana scale (PBSM) to identify strategies that may mitigate the harms related to marijuana use among those young people who choose to use the drug. In the current study, we expand on the initial exploratory study of the PBSM to further validate the measure with a large and geographically diverse sample (N = 2,117; 60% women, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 37 publications
4
66
1
7
Order By: Relevance
“…Although Treloar et al (2015) dropped a manner of drinking item ("drink shots of liquor") from the original measure (Martens et al, 2005) for psychometric reasons, we found that this item can be maintained by modifying the item to be consistent with the remaining items ("avoid drinking shots of liquor"). Marijuana PBS use was assessed using the 17-item version (Pedersen et al, 2017) of the Protective Behavioral Strategies-Marijuana Scale (Pedersen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Although Treloar et al (2015) dropped a manner of drinking item ("drink shots of liquor") from the original measure (Martens et al, 2005) for psychometric reasons, we found that this item can be maintained by modifying the item to be consistent with the remaining items ("avoid drinking shots of liquor"). Marijuana PBS use was assessed using the 17-item version (Pedersen et al, 2017) of the Protective Behavioral Strategies-Marijuana Scale (Pedersen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The PBSM was developed and validated in our prior work (Pedersen et al, 2016a; 2017a). We utilized the brief version of the scale (the PBSM-17), which contains 17 items from the larger 36 item bank that were determined with item response theory analyses to be free from bias regarding gender (male/female), race (White/non-White), ethnicity (Hispanic or Latino(a)/non-Hispanic or Latino(a), and state legalization status (i.e., whether respondents lived in states that had laws regarding legal recreational marijuana or not) in a large young adult college sample.…”
Section: Methodsmentioning
confidence: 99%
“…The scale displayed adequate internal reliability (α = 0.95). Scores on the PBSM were computed as a continuous value by summing responses and converting raw scores to T-scores as advised by Pedersen and colleagues (2017a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These consistent findings underscore the importance of understanding manners of drinking beyond quantity and frequency, particularly considering that some protective behavioral strategies, such as stopping/limiting drinking, have demonstrated equivocal relations to alcohol‐related outcomes (see Pearson, 2013). Similar harm‐reduction strategies exist for manner of cannabis use, including avoiding mixing with alcohol and avoiding cannabis concentrates (Pedersen et al, 2017). Thus, some manners of SAM use may lead to more negative outcomes than others, and this may depend on the use of a specific product (e.g., liquor vs. beer) and/or the use of multiple products.…”
Section: Present Studymentioning
confidence: 98%